Exploring the Effect of Polymer Addition to the Room Temperature Synthesis of Colloidal Lead Halide Perovskite for Better Stability, Higher Passivation, and More Uniform Particle Size - Darwish, Elshaimaa; Elia, Jack; Batentschuk, Miroslaw; Osvet, Andres; Brabec, Christoph (Advanced Engineering Materials, 2025)
In recent years, metal halide perovskites have emerged as a promising alternative to existing semiconductor materials in many applications due to its appealing properties. Despite perovskite huge potentials in many applications, they are still suffering from different kinds of stability issues that are hindering their marketability. Several attempts to stabilize perovskites including polymer encapsulations and inclusions of perovskite materials into polymer matrices due to the stability against moisture that the polymer can offer. Nevertheless, the polymer is acting as an unreactive component without any role into enhancing the optical properties of the studies metal halide perovskite. This study examines the incorporation of the polymer BUTVAR (polyvinyl butyral [PVB]) in the production of various perovskite structures at room temperature: CsPbBr3, Cs2PbBr5, FAPbBr3, and MAPbBr3. The study demonstrates that the incorporation of the polymer solution enhances the optical characteristics and improves the shape uniformity of the resultant perovskite material without altering the inherent structure of the original perovskite material. Furthermore, it improves the durability of the acquired particles against UV irradiation.
CRIS-Team Scopus Importer:2025-04-11
Keywords: perovskite nanocrystals; perovskite nanoparticles higher passivation; perovskite stability; polymer addition to perovskite nanocrystal synthesis; room temperature synthesis